Dinamika Perkembangan Politik Nahdatul Ulama Pasca Khittah Tahun 1984-1999 - Syaekhu Rakhman (HEURISTIK: Jurnal Pendidikan Sejarah, 2021)
Dynamics of Political Development Nahdatul Ulama Post Khittah 1984-1999. This study aims to determine the dynamics of the development of the post-khittah ulema of the ulama in 1984-1999, in addition to that the writer also expects the reader to understand the political development of the NU. The research uses historical research methods. The method used is heuristics, criticism/ verification, interpretation, and historical writing. The results of the study understood the background of the nationalism renewal movement in Indonesia the birth of the Nahdatul Ulama organization in Indonesia, after the NU Khittah which returned to the path of the social religious organization led by Abdurahman Wahid formed NU in the creation of democracy and reform in the country.